The effect of carboxymethyl cellulose and glycerol addition on the biodegradability of cassava starch-based biofilms - Munfarida, Siti; Simamora, Gevbry Ranti Ramadhani; Arista, Yuvita Lira Vesti; Imani, Syarifah Aulia Rahmah; Firdaus, Rizqi Alreza Cahaya; Naibaho, Lasma Barbara (Journal of Tropical AgriFood, 2026)
The growing concern over plastic pollution has accelerated the development of biodegradable packaging materials derived from natural polymers. Cassava starch has been widely studied as a potential raw material because of its abundance and biodegradability. However, its properties are often modified with additives such as carboxymethyl cellulose (CMC) and glycerol to improve film performance, which may influence its biodegradation. This study aimed to investigate the effects of different concentrations of CMC and glycerol on the biodegradability of cassava starch-based biofilms. Biofilms were prepared using three levels of cassava starch (5, 10, and 15 g), three concentrations of CMC (1, 2, and 3%), and three levels of glycerol (6, 9, and 12 mL). Thebiodegradability test was performed using the soil burial method for seven days, with weight loss as the primary parameter.The results showed that all biofilm samples achieved more than 60% degradation within seven days, thus meeting the Indonesian National Standard (SNI) for biodegradability. At low starch concentrations (5 g), the addition of higher CMC and glycerol levels reduced biodegradability due to matrix compaction and reduced porosity. At 10 g starch, biodegradability was more stable, with several formulations reaching 100% degradation by day seven. The highest starch concentration (15g) yielded the best results, with nearly all formulations reaching complete biodegradation, supported by sufficient substrate availability and synergistic interactions betweenCMC and glycerol. Overall, the findings indicate that starch concentration plays a dominant role, whereas excessive CMC and glycerol can slow degradation by limiting microbial accessibility.